Development of Arene Ruthenium Antitumor Complexes - Su, Wei; Tang, Zhaofeng; Li, Peiyuan (Mini Reviews in Medicinal Chemistry, 2016)
The organometallic arene ruthenium complexes are rapidly advancing. In particular, the organoruthenium complexes of the type [(η6-arene)Ru(X)(Y)(Z)] have attracted increasing attention for their special structures and properties. This review is focused on the recent developments of [(η6- arene)Ru(X)(Y)(Z)]-typed complexes incorporating various biologically active ligands, which are important in the exploration of novel multi-targeted organometallic anticancer drugs.
Keywords: Ruthenium